Recognition and Legal Protection of Customary Law Society over Land - Sembiring, Rosnidar; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2017)
This paper aims at determining the recognition and legal protection of indigenous and tribal peoples on land and natural resources in the perspective of legislation. It uses normative research with literature identification approach, legislation such as Law Number 5 of 1960 on the Basic Regulations of Agrarian Principles (BRAP), and other laws and relevant regulations to this research. The data collected from primary, secondary and tertiary legal materials are analyzed qualitatively, systematically arranged and presented descriptively. Basically the recognition and legal protection of indigenous and tribal peoples has been determined in Article 3 of the BRAP and Article 18 B paragraph (1) of the 1945 Constitution and other sect oral laws and regulations, it is just that there is no synchronization or harmonization between various sectoral laws and regulations governing the recognition and protection of the rights of indigenous peoples.